The Hypodense Focus in the Petrous Apex: A Potential Pitfall on Multidetector CT Imaging of the Temporal Bone - Moser, T.; Veillon, F.; Sick, H.; Riehm, S. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: Hypoattenuated foci in the otic capsule are routinely identified on multidetector CT (MDCT), particularly in pediatric patients. We aimed to describe and characterize the hypoattenuated focus in the anterior otic capsule.MATERIALS AND METHODS: We first reviewed histologic sections of the temporal bone from 8-month-old fetuses to determine the nature of the hypoattenuated focus in the anterior otic capsule. A cadaver collection of skull bases from fetuses and neonates (n = 19), infants (n = 24), and young children (n = 23) were then studied with MDCT to determine the developmental evolution of this hypoattenuated focus in relation to the petrous apex. We specifically looked for the hypoattenuated focus in the anterior otic capsule, the development of the petrous apex, and the presence of other hypoattenuated foci in the fissula ante fenestram and middle otic layer.RESULTS: The hypoattenuated focus in the anterior otic capsule corresponded histologically to a cancellous bone trabecula emanating from the middle otic layer and directed toward the petro-occipital fissure. At this level it was covered with a cartilaginous cap. The hypoattenuated focus was observed in all of the fetuses and in all of the postnatal subjects younger than 4 months of age and was always associated with hypoattenuated foci of the middle otic layer and the fissula ante fenestram. This hypoattenuated focus became less obvious as the petrous apex developed.CONCLUSION: The hypoattenuated focus in the anterior otic capsule should be recognized as a normal variant in pediatrics. It could represent a relic from the development of the petrous apex.